THE EFFECTIVENESS OF SCREENCAST-O-MATIC ON STUDENT SPEAKING ABILITY AT MA DARUL FATH PANGKEP - Azizah, Nurul; Qalbi, Nur; Azis, Awalia (FKIP Unismuh Makassar, 2021)
This research aimed to know the speaking ability students when use the Screencast-O-Matic Application at the second grade of MA Darul Fath Pangkep. This research utilized a pre-experimental research method with a quantitative approach which involved 15 samples of the students in the Eleven class IPS at MA Darul Fath Pangkep. This research instrument is a picture of place they had to describe with oral presentation. The research result shows an improvement in the students' speaking ability expecially in fluency after recognize and use the Screencast-O-Matic Applications. It proved the post- test mean score was more significant than the pre-test (71.66>65.33). From the t- test researcher found, the value of the t-test was more excellent than the t-table (4.03>2.14479) at the level of significance 0.05 with the degree of freedom (df) = 14, which means that there was a significant difference between students' speaking before and after applying Screencast-O-Matic. It is also said that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. The result of the research was effective in students' speaking fluency.